Age representation in parliaments: Can institutions pave the way for the young?. Issue 3 (19th March 2018) - Stockemer, Daniel; Sundström, Aksel
Abstract : Middle-aged to senior men of the ethnic majority and higher income groups are generally overrepresented in parliaments. While research on group representation has examined issues of gender, economic standing, and, more recently, ethnicity, few studies examine age groups. We argue that the design of political institutions influences the share of young adults in parliaments across nations and hypothesize that the electoral system type, age candidacy requirements, and quotas influence the share of younger deputies in national parliaments. Analyzing an original data set with a global cross-national sample, we find that proportional representation and giving candidates the right to stand in elections as early as possible (i.e. at the age of 18) matter. In contrast, quota provisions for youths are currently too selectively applied to increase the percentage of young deputies in parliament.